A low-power pseudo-dynamic full adder cell for image addition. (October 2020) - Sadeghi, Ayoub; Shiri, Nabiollah; Rafiee, Mahmood; Rahimi, Parisa
Abstract: Integrated circuits (ICs) employ static and dynamic logic to improve performance and scalability. This paper presents a new circuit design approach named pseudo-dynamic logic (PDL), which shows the advantages of both static and dynamic cells. The PDL is evaluated by using a new full adder cell with 18 transistors. In the presented full adder, gate diffusion input (GDI), transmission gate (TG), and float techniques are combined, and pull-up or pull-down networks are changed into a new configuration so that the number of transistors and internal nodes will decrease. Post-layout simulations and digital image addition are performed to evaluate the real environment and practical application of the cell. Peak signal to noise ratio (PSNR), mean square error (MSE), and structural similarity index metric (SSIM) are calculated to study the cell performance in image processing. Compared to the dynamic and static circuits, the proposed PDL-based full adder cell performs better, and the results validate its effectiveness.